Megaloblastic anemia as a result of an abnormal transcobalamin II (Cardeza). - Haurani, F I (1979)
A 34-year-old Black woman had severe megaloblastic anemia in childhood. Initially, and over the years, she responded well to massive doses of parenteral cobalamin (Cbl) or oral folic acid. Metabolic reactions involving Cbl and folate enzymes were normal during both relapse and remission except for the absence of thymidylate synthetase in relapse. Amino acid analyses of urine and plasma showed no significant abnormalities. Neither cystathionine, homocystine, formiminoglutamic acid, nor methylmalonic acid was detected in the urine. The serum Cbl level was repeatedly elevated even when the patient was receiving only folic acid therapy. The elevation of the vitamin in the serum was found to be a result of markedly increased levels of transcobalamin II (TC II), as identified by several physicochemical techniques. The patient's TC II-Cbl shared immunologic properties with normal TC II but did not facilitate or impede the uptake of Cbl or Cbl bound to normal TC II, respectively, by human cells.